Cyclic Voltammetry, Relativistic Dft Calculations and Biological Test of Cytotoxicity in Walled-Cell Models of Two Classical Rhenium (I) Tricarbonyl Complexes with 5-Amine-1,10-Phenanthroline - Gacitua-Santalices, M; Gacitua-Santalices, M (Elsevier B.V., 2019)
fac-[Re(CO)3(5-amine-1,10-phenanthroline)Cl or Br] (D1 and D2) were synthesized and characterized. D2 was obtained by al alternative method. The electrochemical reaction mechanisms of both D1 and D2 corresponded to EEC for reduction, and ECE for oxidation. Moreover, geometry, electronic, and luminescent properties were analyzed by relativistic DFT and TD-DFT calculations. We determined the lability of –Cl and –Br by a Morokuma–Ziegler analysis. We found that these compounds were less toxic than the ligand alone, and it depends on the cell model tested, where bacteria seem to be more susceptible than yeasts. © 2018